Self‐esteem and peer‐perceived social status in early adolescence and prediction of eating pathology in young adulthood - Smink, Frédérique R.E. (Int J Eat Disord, 2018)
OBJECTIVE: Self‐esteem is implied as a factor in the development of eating disorders. In adolescence peers have an increasing influence. Support for the role of self‐esteem in eating disorders is ambiguous and little is known about the influence of social status as judged by others. The present study investigates whether self‐esteem and peer status in early adolescence are associated with eating pathology in young adulthood. METHOD: This study is part of TRAILS, a longitudinal cohort study on mental health and social development from preadolescence into adulthood. At age 11, participants completed the Self‐Perception Profile for Children, assessing global self‐esteem and self‐perceptions regarding social acceptance, physical appearance, and academic competence. At age 13, peer status among classmates was assessed regarding likeability, physical attractiveness, academic performance, and popularity in a subsample of 1,007 participants. The Eating Disorder Diagnostic Scale was administered at age 22. The present study included peer‐nominated participants with completed measures of self‐perception at age 11 and eating pathology at age 22 (N = 732; 57.8% female). RESULTS: In a combined model, self‐perceived physical attractiveness at age 11 and peer popularity at age 13 were inversely correlated with eating pathology at 22 years, while likeability by peers at age 13 was positively related to eating pathology. DISCUSSION: Both self‐perceptions and peer status in early adolescence are significant predictors of eating pathology in young adults. Specific measures of self‐esteem and peer‐perceived status may be more relevant to the prediction of eating pathology than a global measure of self‐esteem.